Brand Trust, Celebrity Endorser, and Product Bundling on Purchasing Interest and Its Impact on Decisions to Purchase Starbucks Drink at Pekanbaru - Amin, Amirudin M.; Wijaya, Junardi (First Ciera Publisher, 2024)
This research aims to determine and analyze the influence of brand trust, celebrity endorsers and product bundling on purchasing interest and purchasing decisions for Starbucks drinks at Pekanbaru. The population in this study is all residents of the city of Pekanbaru in 2023, the number of which is unknown. Furthermore, with a sampling technique using the Roscoe Formula, a sample size of 100 respondents will be obtained and an accidental sampling technique will be used in sampling. Data analysis in this study used the second-generation multivariate data analysis method or SEM (Structural Equation Model) using PLS (Partial Least Square). Based on the research results, the results show that brand trust has a positive and significant effect on buying interest, celebrity endorsers have a positive and not significant effect on buying interest, product bundling has a positive and not significant effect on buying interest, brand trust has a positive and significant effect on purchasing decisions, celebrity endorsers has a negative and insignificant effect on purchasing decisions, product bundling has a positive and insignificant effect on purchasing decisions and purchase interest has a positive and significant effect on purchasing decisions for Starbucks drinks Pekanbaru.